Predictors of Use of Contraception among Married Women of Reproductive Age in a Rural Area of Nepal - Chaudhary, Tanuja Kumari; Dangol, Bhwan Kumari; Rai, Lalita; Rai, Mana Kumari (Journal of Advanced Academic Research, 2017)
Background: Universal access to family planning is a human right, central to gender equality and women’s empowerment, and a key factor in reducing poverty. Use of contraception can prevent pregnancies related complication, helps in improving the health of mother and children and improve quality of life. Objective: to find out the predictors of use of contraception among married women of reproductive age (15-49 years). Methods: A descriptive cross-sectional study was adopted to find out the predictors of use of contraception among married women in Morang District. Cluster Random Sampling technique was used and sample size was 281. Data was collected by face to face interview technique by pretested questionnaire. Chisquare, bivariate, multivariable logistic regression model was used, and statistical significance was determined with a 95 % confidence level. Results: Mean age of the respondents was 29.52±5.64 years. Current contraceptive prevalence rate was 39.9%. The significant predictors associated with use of contraception were education status of husband (Adjusted Odd Ratio [AOR]=0.331, 95% CI= 0.144-0.759), being desire of children (AOR=2.564, 95%CI=1.060-6.198), spousal communication on contraception (AOR=5.120, 95%CI=2.460-10.656), husband approval on contraception (AOR=8.048, 95%CI=4.047-16.006), and prior use of contraception (AOR= 0.122, 95% CI=0.055-0.272). The common barriers of utilization of contraception were husband disapproval (57.4%) followed by fear of side effects (29.6%). Conclusion: Contraceptive prevalence rates were low. So, continued joint efforts are required to increase use of contraception to improve maternal and child health. It is recommended to involve male in family planning. Journal of Advanced Academic Research, Vol. 3, No. 3, 2016, page: 89-99